Combined impact of prediabetes and fatty liver index on cardiometabolic outcomes and mortality in middle aged adults: a nationwide cohort study - Lyu, Young Sang; Park, Minae; Kim, Hee Kyung; Park, Sojeong; Park, Ji Yong; Hong, A Ram; Yoon, Jee Hee; Jeong, Seogsong; Yoon, Youngmin; Kim, Jin Hwa; Kim, Sang Yong; Kang, Ho-Cheol; et al. (Cardiovascular diabetology, 2025)
Background To investigate the combined effect of prediabetes and fatty liver index on incident diabetes (DM), major adverse cardiovascular events (MACE), and mortality in middle-aged adults. Methods A nationwide cohort study was conducted involving 1,182,751 middle-aged adults aged 40 to 65 years, all of whom had no history of diabetes or cardiovascular disease. The primary outcomes of our study included incident DM, composite MACE and all-cause mortality. Results Among the participants, 24.6% were diagnosed with prediabetes, while 8.8% had FLI ≥ 60 at baseline. Both conditions independently increased the risk of incident DM, composite MACE, and all-cause mortality. Stratification based on the presence of prediabetes and FLI ≥ 60 showed that their combination posed the highest risk for outcomes, even after adjusting for relevant covariates. For incident DM, the odds ratios (ORs) with 95% confidence intervals (CI) were as follows: 3.75 (3.69–3.81), 2.35 (2.29–2.42), and 6.80 (6.62–6.98) for prediabetes with FLI < 60, normoglycemia with FLI ≥ 60, and prediabetes with FLI ≥ 60, respectively. For composite MACE, the ORs (95% CI) were 1.02 (1.00–1.05), 1.23 (1.17–1.28), and 1.27 (1.21–1.33) for prediabetes with FLI < 60, normoglycemia with FLI ≥ 60, and prediabetes with FLI ≥ 60, respectively. For all-cause mortality, ORs (95% CI) were 1.12 (1.08–1.15), 1.51 (1.43–1.59), and 1.69 (1.60–1.79) for prediabetes with FLI < 60, normoglycemia with FLI ≥ 60, and prediabetes with FLI ≥ 60, respectively. Conclusion The coexistence of prediabetes and FLI ≥ 60, which is a surrogate marker of hepatic steatosis, demonstrated a combined effect, additively increasing the risk of incident DM, composite MACE, and all-cause mortality in middle-aged adults. Trial registration Not applicable (retrospectively registered). Graphical abstract